Use of deferasirox (Exjade) for iron overload in peritoneal dialysis patients. Issue 9 (22nd August 2018) - Yii, Erwin; Doery, James CG; Kaplan, Zane; Kerr, Peter G
ABSTRACT: A 54 year old male with b‐Thalassemia major developed ESRD and was managed with continuous ambulatory peritoneal dialysis. Although not able to be transfused due to high titre red cell antibodies he did require management of iron overload. Deferasirox (Exjade) was administered orally. There was concern that excretion of iron via the peritoneal dialysate may raise the risk of iron‐dependent infections (Yersinia and Rhizopus).Whilst receiving Exjade 1000mg /day, a total collection of 12.7L of peritoneal dialysate was collected over a 24 hour period by the patient. The dialysate total iron levels were measured by ICP‐MS at 0.46mmol/L which equates to 0.33mg of Fe in total. Over a 6 month period his serum ferritin fell from 3869μg/l to 1545μg/l. There were no episodes of peritonitis. Since only 7‐8% of the deferasirox and iron complex is excreted through the urine, the amount of Fe seen in the patient's dialysate might be expected to be up to 1.5‐1.6mg. Yet, the results of the Fe levels in the patient's PD fluid was a meagre 0.33mg, about five times lower than expected.Whilst only moderately effective at a dosage of 1000mg/day, deferasirox may be a safe agent for iron removal in iron overloaded peritoneal dialysis patients, as relatively low dialysate iron levels reduces the risk of Yersinia and Rhizopus infection.